Maternal high fat diet compromises survival and modulates lung development of offspring, and impairs lung function of dams (female mice) - Smoothy, J.; Larcombe, Alexander; Chivers, E.K.; Matthews, V.B.; Gorman, S. (BMC, 2019)
© 2019 The Author(s). Published in Respiratory Research.